Knowledge contributions from physical education to early childhood education at the University of Antioquia (Impetus, 2025)
The present research reflects on the knowledge that can be contributed from Physical Education to Early Childhood Education in the context of the University of Antioquia (Medellín, Colombia). This university offers a program that develops theoretical and practical elements to support the comprehensive development of early childhood, based on knowledge specific to the field. A space for contextualization is thus presented, allowing for the recognition of political and socio-cultural aspects that create opportunities for the existence of the Early Childhood Education Segment within the Recreational Sports Program at the University of Antioquia, moving from a global perspective to a local and institutional level. The study was conducted using the qualitative methodology known as archaeology, drawing from the notions proposed by the Grupo Historia de la Práctica Pedagógica en Colombia. Among the key findings, the research highlights the recognition of the multiple types of knowledge that the Recreational Sports Program contributes from Physical Education to Early Childhood Education, based on theoretical aspects narrated by teachers and families. This allowed for an understanding of the meaningful learning experiences of those attending the program and the acknowledgment of these aspects as significant contributors to the comprehensive development process of young children. Regarding contributions from practices, families and teachers expressed their recognition of the guiding activities incorporated in the program’s curricular guide.
Keywords: Physical education; early childhood education; knowledge; university context